2005
DOI: 10.1016/j.joca.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of differential gene expression in temporomandibular joint condylar cartilage after experimentally induced osteoarthritis

Abstract: This study provides a new gene expression profile of the progression of OA. Further study of these OA-related genes may provide new insights into understanding the molecular mechanisms underlying OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 36 publications
0
53
1
Order By: Relevance
“…More specifi cally, it is possible that similar molecular pathways that are activated during OA cause a different outcome in the TMJ compared with the knee. For example, in both OA of the TMJ and OA of other joints, it has been reported that there is an increase in apoptosis [Aigner et al, 2004;Meng et al, 2005]. However, in the healthy mandibular condylar cartilage, there is a percentage of cells that normally undergo apoptosis [Huang et al, 2004].…”
Section: Differences In the Progression Of Oa In The Knee And Tmj In mentioning
confidence: 99%
“…More specifi cally, it is possible that similar molecular pathways that are activated during OA cause a different outcome in the TMJ compared with the knee. For example, in both OA of the TMJ and OA of other joints, it has been reported that there is an increase in apoptosis [Aigner et al, 2004;Meng et al, 2005]. However, in the healthy mandibular condylar cartilage, there is a percentage of cells that normally undergo apoptosis [Huang et al, 2004].…”
Section: Differences In the Progression Of Oa In The Knee And Tmj In mentioning
confidence: 99%
“…However, the regulatory mechanisms responsible for these alterations have not yet been clarified. It is abundantly clear that gene expression is regulated by genetic alterations such as mutations and by epigenetic mechanisms such as alterations in the DNA methylation status, covalent modifications of core nucleosomal histones and rearrangement of histones 6 7. DNA hypermethylation and histone hypoacetylation are hallmarks of gene silencing, while DNA hypomethylation and acetylated histones, specifically in histone H3 at lysines 9 and 14, promote active gene transcription 8 – 11.…”
mentioning
confidence: 99%
“…It has been considered that, in addition to its normal physiological functions, AQP3 might play a role in the pathophysiology of various diseases. Increased expression of AQP3 mRNA and the presence of AQP3 proteins in different localizations in OA cartilage indicate that they have important roles in OA pathogenesis [24]. Expression of aquaporin in various tissues changes with age.…”
Section: Discussionmentioning
confidence: 99%